Contra los «vicios y corruptelas» del foro tradicional, el funcionario militar - Alina Castellanos Rubio (Cahiers de Civilisation Espagnole Contemporaine)
The construction and consolidation of the Elizabethan State implied the development of a capitalized Administration, the first concretions of which were produced under the Moderate government of the 1840s and 1850s. However, they had to contend with the presence of an archetypal civil servant inherited from the Ancien Régime, the iudex perfectus or perfect judge of the traditional monarchy. This article aims to show that the traditional archetype of the iudex perfectus was gradually replaced in liberal political culture by the model of the military officer as a good administrator and thus capable of personifying the virtues hitherto associated with the 'perfect judge' as the embodiment of the institutions of government: fitness, morality and public concept – to which constitutionalism added adherence to the constitution. Various examples, both normative and institutional, are mobilised to analyse the relationship between the two institutional imaginaries – the traditional and the liberal – in both the peninsula and the colonial Caribbean.